تمثيلات الحرب في الرواية العربية دراسة في رواية عمت صباحا أيتها الحرب لمها حسن - بن جبار نور الهدى (My University, 2024)
Abstract: The Arabic novel has emerged as a powerful tool for documenting historical events, conveying the realities of social conditions, and providing a unique literary experience that engages with the social and political upheavals that have swept across the region. In this transformative role, the novel has become a poignant canvas depicting scenes of violence, torture, destruction, and displacement. A notable example of this genre is Maha Hassan's novel "Good Morning, War," which vividly portrays the grim realities of life in war-torn Syria. Hassan masterfully captures the social and political turmoil that has ravaged the country, giving voice to the suffering of Syrians from all walks of life. ------------------- ملخص: أصبحت الرواية العربية أداة لتوثيق الوقائع ونقل التاريخ، وترجمة الأوضاع الاجتماعية مما أتاح تقديم تجربة أدبية جديدة تتفاعل مع الأحداث الاجتماعية والسياسية التي مرت هبا البلاد، وبهذا تحولت الرواية إلى لوحة تعبر عن مشاهد القتل والتعذيب وصور الدمار والضياع. ومن الأمكنة البارزة على هذا النوع الروائي رواية "عمت صباحا أيتها الحرب" لمها حسن، حيث تنقل الكاتبة واقع الوطن السوري في تلك الحقيقة المشؤومة، مصورة الواقع الاجتماعي والأحداث السياسية التي أدت إلى ما آل إليه الوطن، مجسدة محنة السوريين بجميع فئاتهم -------------------- Résumé : Le roman arabe est devenu un outil puissant pour documenter les événements historiques, transmettre les réalités des conditions sociales et offrir une expérience littéraire unique qui aborde les bouleversements sociaux et politiques qui ont balayé la région. Dans ce rôle transformateur, le roman est devenu une toile poignante décrivant des scènes de violence, de torture, de destruction et de déplacement. Un exemple notable de ce genre est le roman de Maha Hassan « Good Morning, War », qui dépeint de manière vivante les sombres réalités de la vie dans une Syrie déchirée par la guerre. Hassan capture magistralement les troubles sociaux et politiques qui ont ravagé le pays, donnant une voix aux souffrances des Syriens de tous horizons
Keywords: representations of war; acting; cultural representation; représentations de la guerre; jeu des acteurs; représentation culturelle.